2003
DOI: 10.11646/zootaxa.134.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Six new species of Trichogramma Westwood (Hymenoptera: Trichogrammatidae) from a Brazilian forest reserve

Abstract: An electrical suction trap set in a forest reserve in the State of São Paulo, Brazil, was used to collect Trichogramma species. Six new species were collected, namely Trichogramma acuminatum n. sp., Trichogramma alloeovirilia n. sp., Trichogramma parrai n. sp., Trichogramma pusillum n. sp., Trichogramma tupiense n. sp. and Trichogramma zucchii n. sp., which are being described herein.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 509 publications
(9 citation statements)
references
References 0 publications
0
8
0
1
Order By: Relevance
“…Considerando-se que no Brasil estão registradas 14 espécies de Trichogramma (Zucchi & Monteiro 1997), verifica-se que o Horto de Tupi possui uma diversidade alta de espécies, pois das 10 espécies coletadas, seis foram descritas recentemente (Querino & Zucchi 2003)…”
Section: Resultsunclassified
“…Considerando-se que no Brasil estão registradas 14 espécies de Trichogramma (Zucchi & Monteiro 1997), verifica-se que o Horto de Tupi possui uma diversidade alta de espécies, pois das 10 espécies coletadas, seis foram descritas recentemente (Querino & Zucchi 2003)…”
Section: Resultsunclassified
“…bennetti (Velásquez & Terán 1995). Zucchi & Querino, 2003 Diagnosis. Flagelliform setae short, with apex tapering abruptly; intervolsellar process distinctly pointed.…”
Section: Introductionmentioning
confidence: 99%
“…Heliconius butterflies feed on pollen, which allows them to live up to six months (Gilbert 1972). Despite the well-known ecological interactions and evolutionary history of Heliconiini butterflies, only very few studies have identified some of their natural enemies to species level (Guerrieri et al 2010; Querino and Zucchi 2002, 2003a,b; Zhang et al 2005; Zucchi et al 2010). We conducted a study of the egg parasitoid community of Heliconiini butterflies on Passiflora plants in a tropical lowland rainforest in Panama and found that most species of parasitic wasps were not yet described.…”
Section: Introductionmentioning
confidence: 99%
“…The diversity of species is well-described for North America where 60 species of Trichogramma are recorded (Pinto 1999, Zucchi et al 2010). In South America 41 species of Trichogramma are described of which most are recorded in Brazil (28 species) followed by Venezuela (13), Colombia (9) and Peru (7) (Parra and Zucchi 2004; Velasquez de Rios and Teran 1995, 2003; Querino et al 2017; Querino and Zucchi 2003a,b, 2005; Zucchi 1988; Zucchi et al 2010). In Central America 22 species of Trichogramma are recorded and among them only one species, T. panamense Pinto has been described from Panama (Pinto 1999), showing that our two new species are the second and third species records for this country.…”
Section: Introductionmentioning
confidence: 99%